Influence of sawdust addition on the toxic effects of cadmium and copper oxide nanoparticles on Vigna radiata seeds. (15th November 2021) - Subpiramaniyam, Sivakumar; Hong, Sung-Chul; Yi, Pyong-In; Jang, Seong-Ho; Suh, Jeong-Min; Jung, Eun-Sang; Park, Je-Sung; Cho, Lae-Hyeon
Abstract: Studies in the literature concern the toxicity of nanoparticles either in a Petri dish or in agar media-based tests. Therefore, for environmental relevance, individual and binary mixtures of metal oxide nanoparticles (M-NPs) cadmium oxide (CdO-NP) and copper oxide (CuO-NP) were tested in this study for their effect on Vigna radiata in soil with and without the addition of sawdust. Seed germination was 67% in 100 mg CuO-NP in soil without sawdust. Seeds failed to germinate in 100 mg CdO +100 mg CuO-NPs in soil without the addition of sawdust and germination was 83% at the same concentration in soil with sawdust. In sawdust added to soil, when compared with control (soil without M-NPs), the maximum reduction in shoot (82%) and root (80%) length and wet (61%) and dry (54%) weight of plant was recorded in CdO-NP treated soil. Similarly, compared with control (soil without sawdust and M-NPs), the percent reduction in shoot (61%) and root (70%) length and wet (44%) and dry (48%) weight was highest in CdO-NP treated soil not supplemented with sawdust. In a binary mixture test (CdO-NP + CuO-NP), the addition of sawdust promoted the above plant growth parameters compared with individual CdO-NP and CuO-NP tests. Cadmium (511 mg kg −1 for individual and 303 mg kg −1 for binary mixture tests) and Cu (953 mg kg −1 for individual and 2954 mg kg −1 for binary mixture tests) accumulation was higher in plants grown in soil without sawdust. The beneficial effect of sawdust addition was observed in seed germination, plant growth, and metal accumulation. With or without sawdust, the binary mixture of CdO and CuO was antagonistic. These results indicate that sawdust can prevent M-NP-induced toxicity and reduce metal accumulation in plant tissues. Graphical abstract: Image 1 Highlights: Mung bean seeds were exposed to CuO and CdO nanoparticles in pot culture. Individual and binary mixtures of CuO and CdO were tested. Toxicity was assessed with and without the addition of sawdust to the soil. With or without sawdust, the binary mixture of CdO and CuO was antagonistic. Sawdust have the ability to reduce the metal accumulation in plant tissues.